2020
DOI: 10.3390/su12072956
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mixed Reality on Satisfaction and Brand Loyalty in Cultural Heritage Attractions: A Brand Equity Perspective

Abstract: Mixed reality technology is being increasingly used in cultural heritage attractions to enhance visitors’ experiences. However, how the characteristics of mixed reality affect satisfaction and brand loyalty has not been explored in previous research. The purpose of this study is to identify factors affecting satisfaction with mixed reality experiences at cultural and artistic visitor attractions and their influence on brand loyalty, which is connected with management performance. We propose a theoretical model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 117 publications
(174 reference statements)
2
38
0
Order By: Relevance
“…As more people adopt these disruptive technologies, there are clear opportunities for researchers and practitioners to conceptualize virtual multi-sensory experiences and apply them to event marketing. Enhancing the visitor experience by using innovative technologies could lead to positive outcomes and increase the number of visitors, thereby contributing to the economic aspects of sustainability, which is particularly important for curators [108]. Thus, there is reason to explore the elements of virtual experiences that modulate causation and correlation.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…As more people adopt these disruptive technologies, there are clear opportunities for researchers and practitioners to conceptualize virtual multi-sensory experiences and apply them to event marketing. Enhancing the visitor experience by using innovative technologies could lead to positive outcomes and increase the number of visitors, thereby contributing to the economic aspects of sustainability, which is particularly important for curators [108]. Thus, there is reason to explore the elements of virtual experiences that modulate causation and correlation.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Ganesan [21] has indicated that satisfaction, derived from previous experience and then constituting an attitude, is a positive emotional response to the result of a previous experience. Bae et al [22] have shared the idea that satisfaction is an emotional response to purchasing. Orel and Kara [23], focusing on the services industry, have held that customer satisfaction describes the desired result of a service experience, including the assessment of whether the service has satisfied customers' demands and expectations.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…Customer satisfaction is a comprehensive assessment of satisfaction with the experience during the entire process of buying clothes. Based on the prior studies [11,12,[21][22][23], the same items were used for the measurement of customer satisfaction at online and physical stores. Furthermore, five items are included to measure with in the Likert 5 scale, in light of the specific situation of clothes selling.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…For example, a Cleveland Cavaliers' fan who plays an NBA-themed VR game may feel as if he/she played basketball in Rocket Mortgage FieldHouse when he/she was surrounded by various Gatorade signage's in the virtual arena. Additionally, Bae et al (2020) found that the characteristics of mixed reality, which represent presence, at cultural and artistic visitor attractions positively affect brand awareness. This suggests that gamers may recognize an IGA brand further when they feel as if they were in the gaming setting.…”
Section: Telepresencementioning
confidence: 97%